Pharmacokinetics, bioavailability, and excretion of ponazuril in piglets - Wang, Wenxiang; Ma, Yuqiao; Zhang, Yunxiao; Nie, Jingjing; Hu, Daxing; Yang, Weicong; Shen, Yue; Cui, Xinglong; Ding, Huanzhong; Li, Li; Huang, Xianhui (Frontiers in Veterinary Science, 2022)
Ponazuril is a triazine anticoccidial drug which is the main metabolite of toltrazuril in animals, it has excellent activity against many protozoa, including Cystoisospora suis, and has broad application prospects in the control of swine coccidiosis. To evaluate the pharmacokinetic and excretion characteristics of ponazuril, 12 healthy piglets aged 10-14 days were divided into 2 groups for pharmacokinetic studies, which were given 20 mg/kg body weight ponazuril orally and intravenously, respectively. And 6 other piglets were housed individually in metabolic cages and given the same oral dose of ponazuril. After administration, the concentration of ponazuril in plasma, fecal, and urine samples collected was determined using high-performance liquid chromatography (HPLC). The plasma concentration profiles of ponazuril obtained after intravenous and oral administration were analyzed simultaneously by the nonlinear mixed-effects (NLME) model. Following the results, the pharmacokinetics of ponazuril exhibited a Michaelis-Menten elimination with Michaelis-Menten constant Km and maximum metabolic rate Vm of 10.8 μg/mL and 0.083 mg/kg/h. The apparent volume of distribution was calculated to be 735 mL/kg, and the final estimated oral bioavailability was 81%. Besides, cumulatively 86.42%±2.96% of ponazuril was recovered from feces and 0.31%±0.08% from urine during 0-1020h after oral administration. These findings indicated a good oral absorption of ponazuril in piglets with nonlinear disposition and slow excretion largely via feces, implying sustained drug concentration in vivo and long-lasting anticoccidial effects.